The civil non-contractual liability arising from road traffic accidents. Judgement of the ap Barcelona 19 June 2020 - Caamiña Domínguez, Celia M. (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This paper deals with the civil non-contractual liability arising from a road traffic accident in Portugal. The jurisdiction of the Spanish courts by virtue of Regulation (EU) 1215/2012 and the applicability of the 1971 Hague Convention will be analysed